TRANSFORMING CONTACT CENTER WFM THROUGH ARTIFICIAL INTELLIGENCE: IMPLEMENTATION AND IMPACT - Vipin Kalra, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Artificial Intelligence (AI) is fundamentally transforming workforce management (WFM) in contact centers, offering unprecedented capabilities in forecasting, scheduling, and performance optimization. This technical article examines how AI-driven WFM solutions leverage machine learning algorithms and predictive analytics to enhance operational efficiency and service delivery. Through an analysis of key components, including intelligent scheduling systems, real-time performance monitoring, and automated coaching mechanisms, we demonstrate how AI integration can reduce operational costs while improving service levels and agent satisfaction. The article presents implementation strategies, case studies, and best practices derived from early adopters while also addressing critical challenges in system integration and change management. By exploring emerging trends and future developments in AI-powered WFM, this comprehensive review provides contact center leaders with actionable insights for successful AI adoption in their workforce management processes. This article indicates that organizations implementing AI-driven WFM solutions can achieve significant improvements in forecast accuracy, schedule optimization, and resource utilization, ultimately leading to enhanced customer experience and operational performance.